Research on the Commercial Law Guarantee Mechanism for Green Credit in New Energy Enterprises - Li, Jingjie (Pinnacle Academic Press Proceedings Series, 2026)
In the context of climate change and the promotion of energy transformation, the development of new energy enterprises is crucial for achieving sustainable development goals and advancing low-carbon economic restructuring. Green credit has become a key financial instrument for guiding capital toward environmentally friendly projects, yet its effectiveness depends on a sound commercial law framework that can allocate risks, protect the interests of stakeholders, and promote market confidence. This paper explores the commercial law guarantee mechanism for green credit in new energy enterprises. First, it clarifies the core concepts of green credit, commercial law guarantees, and new energy enterprises, and outlines the relevant theoretical foundations in financial law, environmental law, and contract law. Second, it analyzes the current situation and dilemmas of green credit protection in China, identifying deficiencies in legislation, contract design, guarantee structures, information disclosure, risk-sharing arrangements, and dispute resolution mechanisms. On this basis, the paper proposes targeted suggestions, including strengthening top-level legislative design, refining the legal status and obligations of green credit participants, innovating green credit contract models, and establishing a diversified guarantee system that integrates collateral, credit enhancement, and policy support. Furthermore, it advocates improving risk-sharing mechanisms, enhancing regulatory coordination, and optimizing dispute resolution procedures to foster a stable and transparent market ecology for green credit in new energy enterprises.